(untitled) (Philological Studies, 2019)
This paper deals with ways and means of expressing directive meanings in the Croatian language. The introductory part presents the main characteristics of the semantic-pragmatic category as well as its relation to the performativity and the speech act. Next, the variety of the propositional content and the illocutionary force of the imperative utterances are discussed, after which the primary and secondary means of expressing the directive meanings are presented. The central part of this paper suggests a typology for different ways of expressing these directive meanings with regards to the semantic-pragmatic variability of their markers and analyzing their usage in written discourse. The final chapter then presents the corpus analysis of ways and means of expressing the directive meanings on the sample of newspaper commercials.